LUBRICANT COMPOSITION FOR INCREASING WEAR RESISTANCE OF HEAVY-LOADED FRICTION PAIRS (Transport systems and technologies, 2022)
The proposed new lubricating composition, which significantly reduces the wear resistance of the rails and wheels of rolling stock during operation, prevents electrochemical corrosion of friction pairs “wheel – rail” and, most importantly, stabilizes the coefficient of friction at the optimum level after a relatively short operating time.The experiments performed on the friction pair “sample of the bandage material of the railway wheel – a sample of the rail material” at the ratio of hardness at the bandage material (Rockwell hardness, HRC scale - 35.3) to the hardness of the rail material 1,1. Test results show that in the case of industrial lubricant, the BioRail brand, with the addition of nanomaterial friction pair with lower wear hardness of the rail metal sample after three hours in operation was practically not observed. Moreover, the average value of the friction coefficient for three hours of operation had been maintained at the level 0.25, which is optimal for the friction pair “wheel – rail”.
Keywords: lubricating composition, wear resistance, rails, wheels of rolling stock, nanomaterial.